Navigating Polymorbidity in Geriatric Primary Care : A Case of Herpes Zoster and Psychological Stress - Hevy Purwaningtyas, Nuretha; Nur Rakhmani, Alidha; Haikal Ashomadoni, Fajar (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Managing complex health issues in elderly patients within primary care requires a holistic, patient-centered approach. This case report details the presentation and comprehensive management of a geriatric patient suffering from herpes zoster exacerbated by significant psychological stress. A 63-year-old male presented with a five-day history of severe, burning pain and pruritus in his right axilla extending to his back, accompanied by vesicular and bullous lesions on dermatomes T1-T2. Prodromal symptoms included headache, fatigue, anorexia, and myalgia. The patient, a former construction worker, also reported significant psychological distress due to prolonged unemployment and reduced communication with his eldest child, exacerbating his symptoms and impacting sleep. He had a history of varicella, controlled coronary artery disease, and hypertension. The clinical picture was consistent with Herpes Zoster Thoracis 1 Dextra, likely reactivated by age-related immunosenescence and heightened psychological stress. The patient's social determinants of health, including financial strain and family communication challenges, significantly contributed to his stress, impacting his functional status and disease perception. Management included antiviral therapy (acyclovir), pain relief (ibuprofen), and non-pharmacological interventions such as rest, nutritional guidance, and local care. Crucially, empathetic counseling addressed his psychological distress, emphasizing stress management techniques and reinforcing positive coping mechanisms through family support and engaging hobbies. This case highlights the intricate interplay between physical illness and psychosocial factors in elderly patients. A comprehensive family medicine approach, integrating biomedical treatment with an understanding of social, economic, and psychological contexts, is paramount for effective disease management and improving overall patient well-being.